Ответы и объяснения

2012-12-15T18:43:35+00:00

н5.

1) х²+6x-7=0

D=36+28=64

x=1

x=-7

х²+6x-7=(x-1)(x+7)

 

2) х²-7x+6=0

D=49-24=25

x=6

x=1

х²-7x+6=(x-6)(x-1)

 

((x-1)(x+7))/((x-6)(x-1)) = (x+7)/(x-6)

2012-12-15T18:53:20+00:00

№1

4х-3у = 23 *3

3х+11у = 4 * 4

 

12х-9у=69

12х+44у=16              Вычитаем из первой вторую

 

-53у = 53

у = -1

 

подставляем в первое уравнение системы

4х - 3*(-3) = 23

4х+3=23

4х=20

х=5

Ответ : (5;-1)

 

 

2a.

x+3/ -(x-3) + x-3/x+3 = 3/9-x^2

Домножаем 1 дробь на (х+3), 2 на х-3

 

Получаем:

(-((х+3)*(х+3)) + (х-3)(х-3) - 9) / (х-3)(х+3) = 0

 

(-(х^2+9+6x)+(x^2+9-6x)-9) / (x-3)(x+3) = 0    ОДЗ: x \neq +-3

-12x-9 = 0

-12x=9

x= - 3/4